2012
DOI: 10.1007/s11130-012-0280-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Effect of Avocado (Persea americana Mill) Seed in a Hypercholesterolemic Mouse Model

Abstract: Avocado seed contains elevated levels of phenolic compounds and exhibits antioxidant properties. We investigated the effect of Avocado Seed Flour (ASF) on the lipid levels in mice on a hyperlipidemic diet. The concentration of phenols was determined by high-performance liquid chromatography, antioxidant activity was evaluated using the Trolox equivalent antioxidant capacity method, and dietary fiber was measured using the Association of Official Analytical Chemists (AOAC) method. The LD50 of ASF was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 22 publications
6
43
1
8
Order By: Relevance
“…The HCD employed in our study provoked a high level of TC and LDL-c, elevation of the AI, and reduction of HDL-c. Similar results have been reported by other authors, for example (48,49). Also the mentioned authors, in concordance with our results, reported no modifications in the level of TG.…”
Section: Nutrition and Cancersupporting
confidence: 94%
“…The HCD employed in our study provoked a high level of TC and LDL-c, elevation of the AI, and reduction of HDL-c. Similar results have been reported by other authors, for example (48,49). Also the mentioned authors, in concordance with our results, reported no modifications in the level of TG.…”
Section: Nutrition and Cancersupporting
confidence: 94%
“…Avocado seed flour (125, 250, and 500 mg/kg/day, by gavage, for 2 weeks) was administered to HCD mice. The results showed a significant reduction in the levels of TC, LDL‐C, and AI, suggesting the antioxidant and hypocholesterolemic activity of this plant (Pahua‐Ramos et al , ).…”
Section: Effect On Lipid Profilementioning
confidence: 89%
“…It is also known as ‘alligator pear’ or ‘butter pear’ (Lacerda et al , ). Avocado is consumed, not only for its flavor, but also for its high nutritional value and beneficial health effects (Meyer and Terry, ) including hypoglycaemic (Ezejiofor et al , ), antihypertensive (Dzeufiet et al , ), antioxidant (Nagaraj et al , ), anti‐obesity (Monika and Geetha, ), hypolipidemic (Pahua‐Ramos et al , ) (Fig. ), antilithiasis (Wientarsih et al , ), anticonvulsant (Ojewole and Amabeoku, ), antimicrobial (Pradeep et al , ), antiprotozoal and antimycobacterial (Jiménez‐Arellanes et al , ), hepatoprotective (Mahmoed and Rezq, ), antiosteoarthritis (Christiansen et al , ) and chemo‐protective (Paul et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…To the avocados are equally attributed analgesic and anti-inflammatory properties (Adeyemi et al, 2002) and the avocado pulp is also used in various dermatological formulations namely, emulsions for the treatment of dry skin, protective agents against ultraviolet radiation, and anti-aging agents (Korać & Khambholja, 2011). Given the variety of uses that are assigned to ethnobotanical species Persea americana several studies have been conducted in order to unveil their biological activity (Gomez-Flores et al, 2008;Yasir et al, 2010;Pahua-Ramos et al, 2012). For example the characterization of phenolic components and antioxidant activity of hydroethanolic extracts of the avocado skin and seed revealed a predominance of compounds belonging to the group of flavonoids, proanthocyanidins, and hydrocinnamic acids (Kosińska et al, 2012).…”
Section: Introductionmentioning
confidence: 99%